2008
DOI: 10.1002/cncr.23887
|View full text |Cite
|
Sign up to set email alerts
|

Defining potency: A comparison of the International Index of Erectile Function short version and the Expanded Prostate Cancer Index Composite

Abstract: BACKGROUND.Both the 5‐item short version of the International Index of Erectile Function (IIEF‐5) and the Expanded Prostate Cancer Index Composite (EPIC) have been used to assess erectile function. In this study, the authors compared various definitions of potency according to the IIEF‐5 and the EPIC.METHODS.Patients with prostate cancer who had completed the IIEF‐5 and the EPIC within 7 days of each other were included. The Spearman correlation coefficient (rho) was calculated to assess the relation between I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…Regardless of nerve-sparing techniques or therapies, men who had erections scored higher in terms of sexual health. But attaining an erection sufficient for intercourse does not always correlate with high sexual health domain scores, as outlined by Schroeck et al [39 ]. They compared a number of definitions for erectile dysfunction and found that an Expanded Prostate Cancer Index Composite (EPIC) score more than 60 and an International Index on Erectile Function (IIEF) score more than 20 correlated highly with sexual function and should be used to define erectile dysfunction in future studies.…”
Section: Erectile Dysfunctionmentioning
confidence: 87%
“…Regardless of nerve-sparing techniques or therapies, men who had erections scored higher in terms of sexual health. But attaining an erection sufficient for intercourse does not always correlate with high sexual health domain scores, as outlined by Schroeck et al [39 ]. They compared a number of definitions for erectile dysfunction and found that an Expanded Prostate Cancer Index Composite (EPIC) score more than 60 and an International Index on Erectile Function (IIEF) score more than 20 correlated highly with sexual function and should be used to define erectile dysfunction in future studies.…”
Section: Erectile Dysfunctionmentioning
confidence: 87%
“…AUA prostat kanser kılavuz paneli 2007 yılındaki çalışmalarında, prostat kanserinde küratif tedavi sonrasındaki erektil işlevin geçerliliği gösteril-miş yeni anketler ile değerlendirilmesini ve tedavi öncesi erektil işlevlerin mutlaka belirtilmesini önermiştir [23]. Schroeck ve arkadaşları da [24] IIEF skorunun 20 den fazla olmasının cinsel işlevin varlığının göstergesi olduğu ve daha sonraki çalışmalar-da bunun kullanılması gerektiğini belirtmişlerdir. Biz de çalışma-mızda erektil işlev durumunu IIEF ile değerlendirerek işlev kaybı ve Beck depresyon skorları ve uygulanan tedaviler arasında fark olup olmadığını da gözden geçirdik.…”
Section: Discussionunclassified
“…Based on the post-treatment median IIEF-5 score (16.0, range: 6-21) and median total FSFI score at the time of survey response (26.3, range: 2.8-34), we know that both the men and women had some degree of sexual dysfunction as indicated by their score below 20 and 26.55, respectively. 22,23 If the recovering male believes the sexual aspect of the relationship is extremely important but his partner does not, he may feel an unjustified amount of pressure in the relationship to recover. As recovery is not a matter of will alone and stress has been linked to decreased sexual performance, recovery and self-worth may be affected if continually under the impression of disappointing his partner.…”
Section: Discussionmentioning
confidence: 99%